Mengembangkan Basic Kecerdasan Spiritual melalui Religious Culture di Sekolah Vokasi - Surawan; Sarifah, Siti; Dyah Apriliani, Anita (Mu'allim, 2024)
This research departs from the importance of increasing spiritual intelligence through the application of religious culture in schools. The purpose of this study was to determine the application of religious culture in increasing the spiritual intelligence of students at SMK Negeri 1 Sampit. This study uses a qualitative method that produces descriptive data. The subjects in this study were students of SMK Negeri 1 Sampit totaling 7 people and the informants were 2 teachers of Islamic Religious Education, 1 homeroom teacher, and the principal. The results of this study indicate that the application of religious culture at SMK Negeri 1 Sampit, namely (a) 3S (Smile, Greet, Greeting) can be realized by saying "Assalamualaikum" to students who are Muslim and saying "good morning" to students who are non-Muslims. (b) Congregational prayers are held in the mushalla 3 times in congregation. (c) Tadarrus Al-Qur'an is accustomed before starting PAI learning for about 5-10 minutes which is applied through teaching and learning activities in class and can be applied through PRIS extracurricular activities. (d) Dressing up to cover the aurat has been applied by female students who are Muslim because of the effect of the learning methodology applied through the application of tadarrus Al-Qur'an which requires them to dress to cover their aurat.